Training and Certification in Dialysis access. Issue 8 (September 2014) - Ross, John; Dolmatch, Bart; Gallichio, Michael; Gallieni, Maurizio; Slakey, Douglas; Vesely, Tom; Davidson, Ingemar
Decreasing and eliminating the gaps in knowledge, skills, and effective communication are the mainstays for a successful dialysis access training program curriculum and at the core of the human factors training philosophy. Many of these skills can be learned in the simulation environment. Education and training will reduce gaps in knowledge and technical skills, before exposing patients to procedure-related risk. For dialysis access, a reliable workplace environment depends upon a culture where safety and accountability are balanced to recognize the human contribution to success or failure in the complex care of patients with end-stage renal disease. Rigorous testing and certification adds value to the participants and validates the training program.